Designing Collaboration Process Facilitation in Hotel Management Teams to Improve Collaboration Performance. (July 2020) - Fu, Shixuan; Cheng, Xusen; Su, Linlin; Bilgihan, Anil; Okumus, Fevzi
Highlights: We propose a set of structured collaboration process to facilitate smooth collaboration among hotel management teams. Design science research (DSR) approach was conducted to design and evaluate process interventions with regard to collaboration in a hospitality context. Collaboration Engineering was applied as a design theory for group-oriented solutions in the hospitality industry. This is one of the first studies to adopt DSR methodology in hotel management teams. Hospitality groups that deployed the proposed process facilitation reported good collaboration performances. Abstract: This study proposes a structured collaboration process providing procedural guidance to facilitate smooth collaboration among hotel management teams. Design science research (DSR) and action research methodologies were followed to develop and evaluate an effective process facilitation based on collaboration engineering (CE) for group-oriented solutions in the hospitality industry. We interviewed members of the hotel management teams who used our process for insights and feedback and conducted a second-round iteration to optimize the designed artifact. According to the research findings, the designed artifact was perceived as easy to follow. Hospitality groups that deployed the proposed process facilitation reported good collaboration performances. Interviewees listed several merits of our collaboration process, including structured collaboration guidance, strict time control, and idea generation encouragement. As one of the first studies to adopt DSR methodology in hotel management teams, this paper puts forth a valuable approach to collaboration engineering in the hospitality industry.